Giant photon bunching, superradiant pulse emission and excitation trapping in quantum-dot nanolasers - Frank Jahnke (Nature Portfolio, 2016)
Classical light sources are characterized by their intensity and coherence, whereas quantum light sources are described by photon correlations. Here, the authors provide a connection between the two for the case of superradiant emission from quantum dots in a nanolaser.